Should I Bribe? Re-Examining the Greasing-the-Wheels Hypothesis in Democratic Post-Soeharto Indonesia - Irfan Kurniawan; Riyanto Riyanto (Institute for Economic and Social Research, 2020)
During the Soeharto Era corruption was considered to grease the wheels of growth in Indonesia, a country once considered to be the most corrupt country in the world. Indonesia began to experience instantaneous decentralization and democratization after the Soeharto Era abruptly ended. While vastly celebrated, these episodes have their unintended consequence: coercive regulation. We employed the extensive firm-level Large and Medium Manufacturing (Industri Besar Sedang/IBS) census data combined with the Indonesian Democracy Index (Indeks Demokrasi Indonesia/IDI) at provincial level spanning from 2009 to 2015 and found that bribery hampered Indonesian firm output and productivity growth by 9.8% and 12.6%, respectively. These results suggest that the greasing effect has now diminished. Interestingly, we also found that firms located in a province with a better democracy index may experience less damaging effects of corruption. In other words, two firms paying the same value of bribe may obtain different effects depending on where they are located.